2013
DOI: 10.1016/j.jss.2012.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Synergic effect of photodynamic therapy using talaporfin sodium with conventional anticancer chemotherapy for the treatment of bile duct carcinoma

Abstract: Background. Photodynamic therapy (PDT) is an effective laser treatment for locally treating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
1
19
0
1
Order By: Relevance
“…まず胆管癌細胞株 NOZ 細胞を用いて PDT の殺細胞 効 果 を 検 討 し た.1 × 10 5 cell/well で の in vitro 解 析 で は,630 nm パルスレーザー照射後 (総エネルギー密度 60 J/cm 2 ) ,時間の推移とともにアポトーシスが増強した ( Fig.1 15,16) .胆管癌の臨床での 集学的治療を考慮すると,主病巣のみならずリンパ節転 移や遠隔転移も制御する必要があり,通常の抗癌剤との 併用効果も興味を持たれるところであるが,基礎研究結 果からも増強効果は明らかであった 17) .基礎研究の問 題点としては,抗癌剤併用を駆使しても in vivo モデル において完全壊死 (complete respouse: CR) が得られない ことにある [15][16][17] .特に腫瘍辺縁に残存する癌細胞が多 いが,レーザー放射の死角となることも考えられるが, 他に周囲新生血管が豊富であることや,治療抵抗性があ るとされる癌幹細胞の残存なども考えられる . レザフィ リン ® を用いた PDT では vascular shutdown 効果が増強 されている可能性が高いが 14,16,17) ,残存領域の効果につ いてより検討を加える必要がある.近年,糖鎖連結クロ リンを用いて腫瘍集積性を高めた PDT が開発され 28,29) , 胃癌や大腸癌モデルではより高い壊死効果が報告されて いる 29…”
Section: ポルフィマーナトリウム (フォトフリン ® ,ファイザ ー) による Pdt 15)unclassified
“…まず胆管癌細胞株 NOZ 細胞を用いて PDT の殺細胞 効 果 を 検 討 し た.1 × 10 5 cell/well で の in vitro 解 析 で は,630 nm パルスレーザー照射後 (総エネルギー密度 60 J/cm 2 ) ,時間の推移とともにアポトーシスが増強した ( Fig.1 15,16) .胆管癌の臨床での 集学的治療を考慮すると,主病巣のみならずリンパ節転 移や遠隔転移も制御する必要があり,通常の抗癌剤との 併用効果も興味を持たれるところであるが,基礎研究結 果からも増強効果は明らかであった 17) .基礎研究の問 題点としては,抗癌剤併用を駆使しても in vivo モデル において完全壊死 (complete respouse: CR) が得られない ことにある [15][16][17] .特に腫瘍辺縁に残存する癌細胞が多 いが,レーザー放射の死角となることも考えられるが, 他に周囲新生血管が豊富であることや,治療抵抗性があ るとされる癌幹細胞の残存なども考えられる . レザフィ リン ® を用いた PDT では vascular shutdown 効果が増強 されている可能性が高いが 14,16,17) ,残存領域の効果につ いてより検討を加える必要がある.近年,糖鎖連結クロ リンを用いて腫瘍集積性を高めた PDT が開発され 28,29) , 胃癌や大腸癌モデルではより高い壊死効果が報告されて いる 29…”
Section: ポルフィマーナトリウム (フォトフリン ® ,ファイザ ー) による Pdt 15)unclassified
“…(22) The clinical application of PDT will be expanded to other tissues in the near future. (22,23) For the treatment of malignant glioma, talaporfin sodium has progressed to a phase II clinical study, and the safety and therapeutic effects of talaporfin have been reported. (2427) While talaporfin sodium and HpD have a similar structure to that of porphyrin, SLC46A1 probably transports talaporfin sodium as well as HpD through structural recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability assay (13,18,19). The effect of PDT on NOZ cell viability was investigated by an assay of a novel tetrazolium compound [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl) -2H-tetrazolium, inner salt; MTS] (CellTiter96 AQueous One Solution Cell Proliferation Assay; Promega Co, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the synergistic effect when combining T-PDT and anti-cancer drugs was clarified (19) and we applied T-PDT for BDC as a clinical trial (20). However, the induction rate of apoptosis was still limited within 50% and the complete response could not be obtained with these results (18,19). The applied laser apparatus is expensive and, thus, a low-cost apparatus is clinically required.…”
mentioning
confidence: 99%